An Australian evaluation of the tick program awareness among university students - Christopher Foong Dhin Li Wai Suen,; Hau, Choong AW; Chiu, Pin Teo; Andrew, Cheng Siu Ng; Sze, Mei Yong (Universiti Kebangsaan Malaysia, 2012)
Cardiovascular disease is a major cause of death in Australia. The Tick Program by the National Heart Foundation was designed to assist consumers in making healthier food choices. Objective: The aim of our study was to evaluate the awareness of university students regarding the Tick Program as a sustainable approach in preventing the onset of cardiovascular disease (CVD) in youth. Methods Following Ethics Committee approval, a cross-sectional study was undertaken in 2006 to measure university students’ level of awareness of the Tick Program using a self-administered survey form. Inclusion criteria were full-time university students who have lived in Australia for a minimum duration of twelve months and do their own shopping. Students of less than 18 years of age were excluded from the study. Results Of 110 university students surveyed, 97 questionnaires were successfully completed (response rate: 88%). Overall there was a high level of awareness (72.2%) of the Tick program, which was also considered trustworthy by a majority of participants, with a mean rating of 3.87 (on a scale of 1 to 5). Tick-approved products were also considered a healthier choice by participants (mean 4.06 out of 5). Participants were also asked to identify potential barriers limiting the use of the Tick in making purchase decisions. The most important barrier identified to the Tick program was the limited range of Tick-approved products. A significant proportion of respondents also believed there was limited publicity of the program. Conclusions The Tick Program is considered to be trustworthy and the approved products were regarded as healthy, with the results showing that participants have confidence in the Tick Program. This research also highlighted the potential areas for improvement of the Tick Program.